Failure Analysis of a Heat Exchanger Tube - Muhd Zulkifli Md Zain, Muhd Zulkifli (Universiti Teknologi Petronas, 2010)
This report presents failure analysis on carbon steel SA – 179 heat exchanger tube in petrochemical plant. Heat exchanger tube found bulging and burst with vertical crack during plant cold start – up period. These incidents make a delay in plant cold start-up process thus increase the shut down period exceeding estimation days before. Opportunity lost to the plant up to RM 2 million per day excluded maintenance work and retubing cost for the new heat exchanger tubes. The aim of this project is to perform failure analysis on bulging and burst heat exchanger tube as well as determine root cause of the failure incident itself